Electrochemical Methods to Evaluate the Antioxidant Activity and Capacity of Foods: A Review - Haque, Md Azizul; Morozova, Ksenia; Ferrentino, Giovanna; Scampicchio, Matteo (Electroanalysis (New York, N.Y.), 2021)
Antioxidants are an important class of food additives playing the fundamental role of retarding oxidation reactions in food. Although their functional role is well‐established, less clear is their mechanism of action. Electrochemical methods based on cyclic, differential pulse, square wave voltammetry and coulometry allow direct and rapid screening of antioxidant activity. Their main advantages are sensitivity, rapidity, simplicity and the capacity to directly measure the number of electrons transferred by an antioxidant offer advantage over conventional spectrophotometric assays. This review aims to summarize the most recent efforts towards the use of electrochemical methods to evaluate the antioxidant activity of foods.